Perinatal Risk Factors for Neonatal Early-onset Group B Streptococcal Sepsis after Initiation of Risk-based Maternal Intrapartum Antibiotic Prophylaxis—A Case Control Study. (23rd September 2017) - Santhanam, Sridhar; Arun, Sumita; Rebekah, Grace; Ponmudi, Nithya J; Chandran, Jolly; Jose, Ruby; Jana, Atanu Kumar
Abstract: Objectives: To identify the perinatal risk factors for early-onset Group B Streptococcus (EOGBS) sepsis in neonates after inception of a risk-based maternal intrapartum antibiotic prophylaxis strategy in 2004. Design: Case control study. Methods: All newborn with early onset GBS sepsis (born between 2004 and 2013) were deemed to be "cases" and controls were selected in a 1:4 ratio. Results: More than three per vaginal (PV) examinations [odds ratio (OR) 8.57, 95% confidence interval (CI) 3.10–23.6] was a significant risk factors. Peripartum fever (OR 3.54, 95% CI 1.3–9.67), urinary tract infection (OR 2.88, 95% CI 1.08–7.63), meconium-stained amniotic fluid (MSAF) (OR 2.52, 95% CI 1.18–5.37) and caesarean section (OR 1.99, 95% CI 1.16–3.43) were also found to be associated with EOGBS sepsis. Conclusion: Multiple vaginal examinations are the strongest risk factors for peripartum Group B Streptococcal (GBS) sepsis. The association of MSAF and caesarean section indicates that foetal distress is an early symptom of perinatal GBS infection.